PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN PADA GRAND JATRA HOTEL PEKANBARU - Kostanitapi "; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Grand Jatra Hotel Pekanbaru , as for the purpose ofthis study was to determine the effect of service quality and company image on custumersatisfication study at Pekanbaru grand jatra hotel. Service quality and company image as theindependent variable (X1X2) while the custumer statisfaction as the dependent variable (Y).The problem in this research is tghe sale of room service of grand jatra hotel pekanbarfluktuated and tenden to decline each year, does not even reach the sale. Seen from thewas taken of 100 respondens of the population was calculated using the Slovin formula. Thefike was getting from the questionnaire and subsequenly processed to then be tasted withstatistics through SPSS. From the recults which shows that service quality and companyimage have a positive and significant impact on custumer satisfication (study at Grand JatraHotel Pekanbaru)Keywords: service quality, company image on custumer satisfication.